Adoption of a new principle in determining the upper limit of the membership function and its applications - عبير سالم النجار (Journal of Madenat Alelem University College, 2014)
The current study is based on the adoption of a new principle in determining the upper limit of the membership function of belonging that achieves better level of ambition Zk*(x) and reach to solve the optimal minimal steps. This was done by selecting the upper limit of within the limits of fitness. Thereby repealed method of random selection to reduce the top and that has underpinned much of the previous research which guess the upper limit of a function belonging within the limits of the fitness or guessed by past experience. To confirm the credibility of the principle of the new method that has been achieved and clarify the process choice to limit the supreme been resorting to previous research in order to be sure to match the results and find optimal solutions using WinQSB applied . The employ new principle that has been achieved to solve the problem of the transfer of multiple targets for a private sector company in Baghdad and involved in the processing of spark lighting (neon).